The Image of Mansur Khalloj in Hofiz Khorezmi's Work - Amonova Zilola Qodirovna (Universitas Muhammadiyah Sidoarjo, 2022)
Hafiz Khorezmi is one of the poets who lived and worked in Uzbek classical literature in the late 14th and early 15th centuries and left a significant creative legacy. From the poet came a large devon. The ghazal occupies a central place in the Devon. The poet's poems are varied in subject matter. While they describe the creation of the universe, the sanctity of man, and the divinity of love, we can see that they criticize the vices of man and the imperfections of man.